Sustainable human resource management practices, employee resilience, and employee outcomes: Toward common good values - Lu, Ying; Zhang, Mingqiong Mike; Yang, Miles M.; Wang, Yue (Human resource management, 2023)
Extant literature has generated limited understanding of whether and how sustainable human resource management (HRM) will lead to better and more sustainable outcomes, such as enhanced employee well‐being and improved employee performance. Moving toward common good values and drawing on the job demands‐resources model, this study theorizes and tests the relationships among sustainable HRM practices, employee resilience, work engagement, and employee performance. The empirical results of a multilevel and multisource study in the Chinese context provide supporting evidence for our theoretical model. The findings demonstrate that sustainable HRM practices positively affect employee resilience, and lead to a high level of work engagement among employees. Employee resilience also has an indirect effect on employee performance through work engagement. This study, with its theoretical and practical implications, reveals a serial mediation mechanism through which sustainable HRM practices contribute to both employee well‐being and employee performance.